1990
DOI: 10.1007/bf01344312
|View full text |Cite
|
Sign up to set email alerts
|

Schooling behavior of Antarctic krill (Euphausia superba) in laboratory aquaria: Reactions to chemical and visual stimuli

Abstract: Antarctic krill, Euphausia superba, often exhibit abnormal behavior in laboratory aquaria, usually hovering in a stationary position, unresponsive to most external stimuli. In the austral summer of 1985-1986 at Palmer Station on Anvers Island, Antarctica, we provided laboratory conditions which induced E. superba to school in large aquaria. Captive krill swam horizontally and exhibited the full spectrum of behaviors normally displayed while schooling at sea. Schooling krill avoided visually contrasting stimuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 11 publications
4
56
0
Order By: Relevance
“…In one experimental study, the structure of krill swarms did not appear to change in response to water flow but rather to behaviorally induced mechanisms, such as food and predators (O'Brien 1989). In another study, krill were induced to swarm in a tank when a model of a predator was introduced (Strand & Hamner 1990). Divers have observed complex schooling behavior in all life history stages of E. superba, including foraging, feeding, predator avoidance, and mating behavior (Hamner 1984, Naito et al 1986, O'Brien 1987b, Hamner et al 1989).…”
Section: Using Continuous Profiles O F In Vivo Fluorescence and Acomentioning
confidence: 99%
“…In one experimental study, the structure of krill swarms did not appear to change in response to water flow but rather to behaviorally induced mechanisms, such as food and predators (O'Brien 1989). In another study, krill were induced to swarm in a tank when a model of a predator was introduced (Strand & Hamner 1990). Divers have observed complex schooling behavior in all life history stages of E. superba, including foraging, feeding, predator avoidance, and mating behavior (Hamner 1984, Naito et al 1986, O'Brien 1987b, Hamner et al 1989).…”
Section: Using Continuous Profiles O F In Vivo Fluorescence and Acomentioning
confidence: 99%
“…Hamner (1984) observed that E. superba sometimes have whitish individuals (presumably parasitized) positioned behind the school unable to swim as fast as healthy individuals. Strand & Hamner (1990) reported E. superba exclusively forming schools, and the few solitary individuals they captured were almost always damaged and/or parasitized.The low prevalence rates of parasites, castrators, and parasitoids detected in euphausiids in the present study (excepting epibiotic organisms with an apparently negligible effect on the host) indicate how several parasites have to deal with many intermediate and paratenic hosts to infest or infect their definitive hosts and complete their complex life cycles. In other words, population density and swarming behavior of the hosts may control parasite population dynamics.…”
mentioning
confidence: 97%
“…The chemosensory abilities of Antarctic krill enable them to discriminate among particles (Hamner et al 1983). Also, when euphausiids encounter patches of phytoplankton their swimming behavior changes and they aggregate in that patch (Price 1989;Strand and Hamner 1990), facilitating their ability to graze on preferred food.…”
mentioning
confidence: 99%